New variation of scimitar syndrome with tracheal bronchus, upper lobe agenesis, and ventricular septal defect in a child - Yurtsever, İsmail; Yeşilbaş, Osman; Yozgat, Can Yılmaz; Tekin, Eser; Yozgat, Yılmaz (Wiley, 2022)
Scimitar syndrome (SS) is a rare and complex disease charac-terized by cardiovascular and bronchopulmonary malforma-tions. In typical SS, anomalous pulmonary drainage of part orall of the right lung into the inferior vena cava, anomaloussystemic arterial supply of the right lung from either the tho-racic or abdominal aorta, and hypoplasia of the right lungoccur.1Abnormal bronchial anatomy, abnormal diaphragm,hemivertebrae, and genitourinary tract anomalies can alsomanifest in SS.2,3Generally, the symptoms of this syndromeappear 7 months after birth.4According to the literature, therehave been numerous cases where additional features of thetypical syndrome have been reported with Scimitar variants.
Keywords: Right Upper Lobe Agenesis; Scimitar Syndrome; Tracheal Bronchus